Prevalence of high blood pressure and hypertension among children and adolescents in Europe: a systematic review and meta-analysis - Rietz, Helene; Svärdhagen, Gustav; Wühl, Elke; Lurbe, Empar; Brunström, Mattias (Archives of disease in childhood, 2025)
Objective This systematic review and meta-analysis aims to estimate the prevalence of high blood pressure (BP) and hypertension among European children and adolescents (1990-present). - Methods We included population-based cross-sectional and cohort studies reporting BP in children (≤18 years) from European countries, excluding studies from electronic health records or specialist care referrals. PubMed was searched on 27 January 2025. Risk of bias was assessed with the Hoy et al tool, and data were pooled using random-effects meta-analysis. The main outcomes were pooled prevalence of high BP and hypertension. - Results We analysed 56 studies (n=179 279, mean age, 12 years) from 18 European countries. The prevalence of high BP was 8% (95% CI 7% to 10%), higher in boys (7%, 95% CI 6% to 9%) than in girls (5%, 95% CI 4% to 7%). Among children with obesity, prevalence was 23% (95% CI 18% to 29%) vs 6% (95% CI 4% to 9%) in children without obesity. Prevalence was highest in 10-13 years old (8% (95% CI 5% to 13%) compared with 6% (95% CI 4% to 8%) and 6% (95% CI 3% to 9%) in 3-9 years old and 14-19 years old, respectively. The prevalence of hypertension was 4% (95% CI 3% to 5%). Risk of bias was judged to be moderate or high for most studies, with variability in BP measurement methods. - Conclusions The prevalence of high BP and hypertension among European children and adolescents is considerable, particularly among those with obesity, where one-fourth has high BP. It is more common in boys and peaks during puberty. These findings should be interpreted with caution due to methodological limitations of the included studies.